OLYMPIAQUIZ: board game-based learning object for teaching the history of Olympic Athletics - Denise Dandara Gomes de Carvalho Severo,; Iara Rodrigues Abreu,; Welliton da Silva Belém,; André Luiz Barbosa Marinho,; Mateus Silva Gonçalves,; Diana Ketlem Paula do Nascimento,; Daniela Tissuya Silva Toda,; Silva, Kaio Alexandre da (International Journal for Innovation Education and Research, 2022)
The present work aimed to insert strategic tools with the use of board games in order to assist and facilitate learning about the history of Olympic games, highlighting the importance of working the Olympic context in the disciplines of Physical Education and History. Even with the advance of technology, teachers still find it difficult to teach their students in the classroom, because distractions and lack of interest are commonplace in the school environment. Thus, a systematic review of the literature was conducted from journals and academic articles, aiming at a deeper study on the theme addressed. With this, OlympiaQuiz was created, a board game focused on teaching the Olympic Games, exploring the social and historical context of the time, to encourage learning through games.